Non-alcoholic fatty liver disease (NAFLD) and mental illness: Mechanisms linking mood, metabolism and medicines - Gangopadhyay, Anwesha; Ibrahim, Radwa; Theberge, Karli; May, Meghan; Houseknecht, Karen L. (Frontiers in Neuroscience, 2022)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the world and one of the leading indications for liver transplantation. It is one of the many manifestations of insulin resistance and metabolic syndrome as well as an independent risk factor for cardiovascular disease. There is growing evidence linking the incidence of NAFLD with psychiatric illnesses such as schizophrenia, bipolar disorder and depression mechanistically via genetic, metabolic, inflammatory and environmental factors including smoking and psychiatric medications. Indeed, patients prescribed antipsychotic medications, regardless of diagnosis, have higher incidence of NAFLD than population norms. The mechanistic pharmacology of antipsychotic-associated NAFLD is beginning to emerge. In this review, we aim to discuss the pathophysiology of NAFLD including its risk factors, insulin resistance and systemic inflammation as well as its intersection with psychiatric illnesses.